2011
DOI: 10.1208/s12249-010-9556-z
|View full text |Cite
|
Sign up to set email alerts
|

Solid Dispersions of Imidazolidinedione by PEG and PVP Polymers with Potential Antischistosomal Activities

Abstract: Abstract. Solid dispersions have been used as a strategy to improve the solubility, dissolution rate, and bioavailability of poor water-soluble drugs. The increase of the dissolution rate presented by (5Z)-3-(4-chloro-benzyl)-5-(4-nitro-benzylidene)-imidazolidine-2,4-dione (LPSF/FZ4) from the solid dispersions is related to the existence of intermolecular interactions of hydrogen bond type (>N-H ... O<) between the amide group (>N-H) of the LPSF/FZ4 and the ether group (-O-) of the polyethyleneglycol polymer, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…Many hypotheses have been proposed to explain the mechanism by which formulation as a solid dispersion can ameliorate the disadvantageous pharmaceutical properties of drugs. Generally, the major factors that influence drug solubility and dissolution include degree of crystallinity, wettability, and particle size (23). The XRD results indicated that the drug was in an amorphous form within the crystalline polymer matrix.…”
Section: Discussionmentioning
confidence: 99%
“…Many hypotheses have been proposed to explain the mechanism by which formulation as a solid dispersion can ameliorate the disadvantageous pharmaceutical properties of drugs. Generally, the major factors that influence drug solubility and dissolution include degree of crystallinity, wettability, and particle size (23). The XRD results indicated that the drug was in an amorphous form within the crystalline polymer matrix.…”
Section: Discussionmentioning
confidence: 99%
“…SDs prepared with water-soluble polymer carriers are usually soft and sticky and have poor flow properties, which hinders their application in large-scale pharmaceutical formulation. 11,30,31 In this study, SDs prepared with CNPs were not sticky and flowed freely, which may facilitate the downstream processing of solid formulations. Thus, we can conclude that CNP has great potential for clinical application as a novel and promising SD carrier.…”
Section: Resultsmentioning
confidence: 89%
“…[1011121314] Dissolution rates can be improved by particle size reduction, increased wettability through mixing with highly soluble carriers, and maintenance of the drug in the amorphous form. [151617] Although the application of SDs has been reported regularly in the pharmaceutical literature, only a few commercial products rely on the SDs strategy.…”
Section: Introductionmentioning
confidence: 99%